Learning Results Of Long Badminton Services Through The Cooperative Stad Learning Model - Ruslan Ruslan; Apriasari Apriasari; Nurjamal Nurjamal; Hendry Ismawan; Budi Nurhidayat (UNIB Press, 2021)
The service stroke is a technique with a racket that hits the shuttlecock to another field diagonally to start a game in badminton. In this service training in badminton uses the STAD cooperative learning model which emphasizes the existence of activities and interactions between students to motivate each other and help each other in mastering learning material. The purpose of this study is to improve learning outcomes forehand long service techniques using the STAD cooperative learning model. This type of research is classroom action research. The sample of 33 people was divided randomly into six groups. The research was conducted in II cycles, in one cycle two meetings. Data collection techniques in this study were documentation techniques, observation techniques and student learning outcomes tests that were given at the end of each cycle. The learning outcomes for two cycles using the cooperative learning model stad type in the long service technique for badminton forehand showed an increase in the average learning outcomes of each cycle, the percentage increase in the percentage from pre-cycle to cycle II was 11.30%. The conclusion of this study is that using the cooperative learning model type STAD can improve learning outcomes for badminton forehand long service.